Development of Textured Lead-Free Nbt-Based Piezoelectric Materials in a Matrix, Synthesized by an Alternative Route, Via Templated Grain Growth - Çoban Tetik, Hatice Şule; Suvacı, Ender; Karakaya, Merve; Avcı, A. Murat; Adem, Umut; Adem, Umut; Karakaya, Merve (Springer, 2023)
In this study, (1−x)(K0.5Bi0.5TiO3-BaTiO3)−xNa0.5Bi0.5TiO3 KBT:BT = 2:1 where x = 0.8 (KBT-BT-NBT) (001) textured lead-free piezoelectric ceramics were fabricated using BT template by templated grain growth with tape casting. Unlike the commonly used matrix preparation method, which is the calcination of all raw materials in one step, the matrix phase was prepared in a different way by first preparing KBT, BT and NBT powders separately and then by calcining the mixtures of these powders, so that effect of the matrix, synthesized by this alternative route, on texture development properties was evaluated. In addition, the effect of BT template content on the grain orientation with different sintering temperature and time, structure evolution, phase stability and piezoelectric properties were investigated to assess the materials’ actuating performance. The highest Lotgering factor of 81% was achieved for the textured ceramics with 10 wt% BT templates sintered at 1150 °C for 48 h. Compared to the one-step synthesis method, similar Lotgering factor values were obtained at lower sintering temperatures in the matrix, synthesized by the alternative 2-step method. The highest piezoelectric constant, remnant polarization, strain value and depolarization temperature were also obtained from the same sample, as ~ 190 pC/N, 30 kV/cm, 25% at 50 kV/cm and ~ 165 °C, respectively. The results show that the textured, lead free K0.5Bi0.5TiO3-BaTiO3-Na0.5Bi0.5TiO3 (KBT-BT-NBT) ceramics that are developed by using the matrix, synthesized by the alternative 2-step method, can be very promising lead-free electroceramics for high performance actuator applications.
This work was supported by The Scientific and Technological Research Council of Turkey and Eskisehir Technical University Scientific Projects Commission (Grant Numbers 116M214 and 1709F504)
Keywords: Barium titanate; Calcination; Depolarization; Powders materials